THE EFFECT OF PSAK 72 IMPLEMENTATION, COMPANY SIZE, AND ROA ON THE FIRM VALUE: (Empirical Study on Companies Indexed in LQ-45 during 2017-2020) - Muhammad Fatoni; Agustin Fadjarenie (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study aims to analyze the effect of implementation of PSAK 72, company size, and return on assets (ROA) on the firm value. The sample of this research is companies indexed in LQ-45 during 2017-2020. There were 29 companies selected as samples using the purposive sampling technique. The data used is secondary data collected by documentation techniques. The data is analyzed using statistical analysis using the tools E-Views 10 Program. In analyzing the data, this study used panel data regression statistics with the selected model of the fixed effect model. The results of the hypothesis test show that the implementation of PSAK 72 and ROA have a positive effect on the firm value, while company size has a negative effect on the firm value. In conclusion, positive and significant effect of application of PSAK 72 implies that the particular companies tend to have high firm value. The positive and significant effect of ROA on firm value implies that the higher the ROA in a company, the higher the company’s reputation. Meanwhile, the negative and significant effect of company size indicates that small companies perform better compared to bigger companies.